Enhanced DSSC efficiency using SrAl2O4:Eu2+,Dy3+-modified ZnO nanostructures - Yamac, Halil Ibrahim (Springer, 2026)
In this study, ZnO nanostructures modified with different SrAl2O4:Eu2+,Dy3+ ratios (1-7%) were synthesized using a hydrothermal technique and employed as photoanodes in dye-sensitized solar cells (DSSCs). The structural, morphological, textural, optical, electrochemical, and photovoltaic properties of the prepared photoanodes were systematically investigated using XRD, SEM/EDS, BET, UV-Vis spectroscopy, current density-voltage analysis, and electrochemical impedance spectroscopy. XRD results confirmed that all samples retained the hexagonal wurtzite ZnO structure, while SrAl2O4:Eu2+,Dy3+ addition induced noticeable changes in crystallite size, lattice parameters, morphology, porosity, and optical absorption behavior. Among the investigated compositions, the 3% SrAl2O4:Eu2+,Dy3+-modified ZnO photoanode exhibited the most favorable balance between surface area, optical band gap, charge-transfer behavior, and recombination suppression. As a result, the corresponding DSSC achieved the highest power conversion efficiency of 3.76%, representing a 29.6% improvement compared with pristine ZnO. These findings indicate that SrAl2O4:Eu2+,Dy3+ modification is a promising strategy for improving ZnO-based DSSC photoanodes through combined optical, textural, and interfacial effects.
Keywords: Sensitized Solar-Cells; Nanorod Arrays; Structured Zno; Hydrothermal Method; Photoanodes; Performance; Growth; Nanofibers; Energy; Film